On weakly concircular ï¦- symmetric of ïƒŽ-trans sasakian manifolds - Khairnar, V J; Gaikwad, S B (Recent Research in Science and Technology, 2012)
The purpose of this paper is to introduce a new concept such as weakly concircular ï¦- symmetric ïƒŽ-Trans-Sasakian manifold, and study its properties. A series of corollaries from the theorems are also obtained and a concrete example for the existence of such manifolds is provided.